Study of pressure distribution in compliant coated abrasive tools for robotic polishing - Muhammed Umer. (2012)
A major advantage of using coated abrasive tools is that they are complaint and their geometry conforms to the surface of the workpiece. While much research has been done to reduce polishing force variations by force control and compliance mechanisms, not much work has been done to understand the effect of compliance on the distribution of forces in the contact area of such tools. In this project, pressure distributions were simulated using finite element models developed in ABAQUS CAE software. The simulated distributions were compared to measurements from pressure film sensors for different parameters under robotic polishing, and matched fairly well. Furthermore, the use of Preston's Law to predict finished surface profiles for a flat workpiece was demonstrated. The physical interpretation of such simulated pressure distributions, using Preston's Law, can be used to understand material removal as polishing proceeds. Investigations in this project were limited to using zero horizontal feed rate and flat workpiece surfaces. Further research using non-zero feed rates and curved surfaces will increase the applicability of using such finite element models to predict material removal profiles in complaint coated abrasive tool polishing.